Wuling Mountains Function as a Corridor for Woody Plant Species Exchange Between Northern and Southern Central China - Wang, Congrong; Zhou, Tianyang; Qin, Yuanzhi; Zhou, Gang; Fei, Yanan; Xu, Yaozhan; Tang, Zhiyao; Jiang, Mingxi; Qiao, Xiujuan (Frontiers in Ecology and Evolution, 2022)
Aim Wuling Mountains range from the northeast to southwest in Central China, a region with high habitat complexity and diversity that supports substantial plant species diversity. Connecting the northern subtropics to the mid-subtropics, Wuling Mountains also link the floras of Eastern and South-Western China. Despite a long-standing interest in how important role Wuling Mountains play in species exchange, patterns of plant species diversity in Wuling and their underlying drivers are still not well characterized. Here, the spatial distribution of woody plant species in this region is described and the role the Wuling Mountains play in structuring biodiversity in surrounding areas is explored. Location Wuling Mountains and adjacent regions, China. Methods Detailed distribution data for woody plant species in China were collected and mapped onto a raster grid of the Wuling Mountains and adjacent regions (a total of 820,000 km2) to analyze spatial patterns in species diversity, including α-diversity (species richness) and β-diversity (βsor). Unweighted pair-group method using arithmetic averages (UPGMA) clustering was used to divide the study region based on species composition. Canonical redundancy analysis was used to illustrate spatial patterns and species-environment relationships. Results Mountainous areas in the study region have high species richness as compared to other areas. Species exchanges occurred at a greater rate latitudinally vs. longitudinally, especially in Wuling Mountains. This suggests that Wuling Mountains may be an important ecological corridor for woody species, linking Northern and Southern Chinese floras. The study region was divided into six bioregions based on species composition: the Wuling Mountains Region, Nanling-Xuefengshan Mountains Region, Qinling-Dabashan Mountains Region, Sichuan Basin Region, Yangtze Plain Region and Yungui Plateau Region. Main Conclusions The Wuling Mountains Region acts as an ecological corridor for woody species, linking Northern and Southern China, and fostering biodiversity exchange and conservation in Central China.